2023
DOI: 10.51685/jqd.2023.008
|View full text |Cite
|
Sign up to set email alerts
|

Who speaks and who is heard on Facebook? Political mobilization and engagement patterns of partisanship and gender in Switzerland’s direct democracy

Abstract: This descriptive study investigates political mobilization and user engagement patterns on Facebook and associated partisan and gender discrepancies. It focuses on Switzerland, where political actors frequently seek to mobilize and shape citizens’ opinions before direct-democratic voting on wide-ranging policy issues. Using digital trace data from CrowdTangle, the analysis focuses on the posting frequency and received user interactions of 770 Swiss political actors’ Facebook pages. The analysis period covers 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In their analysis of survey data on offline and online political engagement among first-year college students, Hargittai and Shaw (2013) do not find evidence of a relationship between partisanship and a range of engagements with political content online. An analysis of Swiss political parties' Facebook content revealed discrepancies in user engagement depending on which party shared content, with the most leftand right-wing parties receiving bigger shares in engagement (Maitra and Hänggli Fricker, 2023). Some work has found that political affiliation matters for sharing misinformation on social media (Freiling.…”
Section: Political Affiliation and Content Sharingmentioning
confidence: 99%
“…In their analysis of survey data on offline and online political engagement among first-year college students, Hargittai and Shaw (2013) do not find evidence of a relationship between partisanship and a range of engagements with political content online. An analysis of Swiss political parties' Facebook content revealed discrepancies in user engagement depending on which party shared content, with the most leftand right-wing parties receiving bigger shares in engagement (Maitra and Hänggli Fricker, 2023). Some work has found that political affiliation matters for sharing misinformation on social media (Freiling.…”
Section: Political Affiliation and Content Sharingmentioning
confidence: 99%